2005
DOI: 10.1128/jcm.43.11.5768-5770.2005
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of CHROMagar Candida Medium with Pal's Medium for Rapid Identification of Candida dubliniensis

Abstract: CHROMagar Candida medium is used for the isolation and identification of Candida species, but it does not differentiate Candida albicans from Candida dubliniensis . This differentiation can be achieved by using Pal's agar, which cannot be used in primary isolation. We have combined both media to obtain a new medium that can be used for the isolation and identification of C. dubliniensis in primary cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 16 publications
5
15
1
2
Order By: Relevance
“…This color divergence reinforced the different shade of green described by Schoofs et al (26) for C. dubliniensis. We have not been able to confirm this observation in a consistent way when using the CAC medium provided by CHROMagar (France), with results that are in agreement with recent publications (6,23). In the present study, we have evaluated many stock culture strains, and it has been reported that the dark green color of the colonies may be lost upon repeated subculture or storage (11,25,26).…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…This color divergence reinforced the different shade of green described by Schoofs et al (26) for C. dubliniensis. We have not been able to confirm this observation in a consistent way when using the CAC medium provided by CHROMagar (France), with results that are in agreement with recent publications (6,23). In the present study, we have evaluated many stock culture strains, and it has been reported that the dark green color of the colonies may be lost upon repeated subculture or storage (11,25,26).…”
Section: Discussionsupporting
confidence: 44%
“…The reason for our results may be due to the use of stock culture strains or to the possibility that other brands of CHROMagar could yield different results in the presumptive identification of C. dubliniensis based on the color of the colonies. The identification of this species can be facilitated using CAC supplemented with Pal's agar, as has been recently reported (23). We have observed that CAID2 allowed a differentiation at 48 h between C. albicans, growing as cobalt blue colonies, and C. dubliniensis, growing as turquoise blue colonies.…”
Section: Discussionmentioning
confidence: 68%
“…To our knowledge, only Odds & Davidson (2000) had previously described some C. albicans isolates that formed pink coloured colonies on CAC medium. It has been reported that differentiation between C. dubliniensis and C. albicans clinical isolates can be improved in CH-P agar (Sahand et al, 2005(Sahand et al, , 2009); however, in our hands both media, CH-P and CAC, lacked discriminatory capacity to distinguish both Candida species accurately when dealing with these unusual isolates. Finally, ChromID medium has high sensitivity and specificity to differentiate C. dubliniensis from C. albicans (Eraso et al, 2006b).…”
Section: Discussioncontrasting
confidence: 68%
“…Chlamydospore production was examined by incubating the isolates for 72 h at 30 uC on Pal's agar (Pal, 1997), Staib agar (Staib & Morschhäuser, 1999), Casein agar (Mosca et al, 2003), Cornmeal agar (Sullivan et al, 1995), CHROM-Pal's agar (CH-P) (Sahand et al, 2005), and YNB agar supplemented with galactose 0.025 % (w/v) and methionine (25-100 mg l 21 ) (Citiulo et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation